2015
DOI: 10.5094/apr.2015.062
|View full text |Cite
|
Sign up to set email alerts
|

Development and laboratory evaluation of a compact swirling aerosol sampler (SAS) for collection of atmospheric bioaerosols

Abstract: Inhalation of infectious bioaerosols has been linked to a variety of respiratory diseases. However, efficient sampling techniques to allow high temporal resolution sampling are limited to collect and study bioaerosols in the various occupational and ambient micro-environmental atmospheres. This study introduces a medium flow swirling bioaerosol sampler (SAS) approach that collects atmospheric bioaerosols at the flow rate of 167 Lpm (10 cubic meter per hour). The collection of bioaerosols is achieved through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Many previous studies used wet-lab experimental data to evaluate the cyclone performance based on these three ratios [17,20,[47][48][49][50]. In some experiments, inactive microorganism simulants, such as polystyrene latex (PSL), were applied to test the aerosol-to-hydrosol collection efficiencies of cyclones [15,51,52]. McFarland et al [32] defined the aerosol-to-hydrosol efficiency to be the intrinsic system of the WWC performance parameter with the detection of polystyrene latex spheres.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies used wet-lab experimental data to evaluate the cyclone performance based on these three ratios [17,20,[47][48][49][50]. In some experiments, inactive microorganism simulants, such as polystyrene latex (PSL), were applied to test the aerosol-to-hydrosol collection efficiencies of cyclones [15,51,52]. McFarland et al [32] defined the aerosol-to-hydrosol efficiency to be the intrinsic system of the WWC performance parameter with the detection of polystyrene latex spheres.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In addition, the cyclone performance evaluation with biological particles is a critical performance characterization. A previous study showed that the collection (aerosol-to-hydrosol) efficiency of a cyclonic swirling bioaerosol sampler for an aerosol cut-off size larger than 0.7 lm was 50%, and for that larger than 2 lm was 80% [52]. In another case, the sampling efficiency was tested for two new cyclone-based bioaerosol samplers.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In brief, the AGI-30 impinger was installed and placed on three tangential nozzles with the height of 1.5 m above the ground, and it was operated with 10 mL of phosphate buffer saline (PBS) injected into the Proton sampler (S. Figure 1). The airflow rate of filtration was 12.5 L/min for 30 min [50], and aerosol samples obtained at different locations in dairy herds were transferred into 15-mL centrifuge tubes in a cold box and transported to the laboratory. Primer design and synthesis A total of 69 sequences from different BVDV-1 lineages were obtained from NCBI GenBank database (http:// www.ncbi.nlm.nih.gov/) (S. Table 2) and aligned using the Clustal W program (MEGA 5.0 software).…”
Section: Viruses Cells and Aerosol Samplesmentioning
confidence: 99%
“…Lab-designed air samplers have been developed for a higher enrichment capacity (EC). Wubulihairen et al (2015) introduced an ATH sampler that could apply an inertia impaction method where the EC was 835 for 100-nm particles. Hong et al (2016) studied an electrostatic particle concentrator (EPC) that could capture airborne viruses in a liquid volume of 0.5 mL; however, the EPC had a low EC of 8750 for a 100-nm airborne virus.…”
Section: Introductionmentioning
confidence: 99%